2020
DOI: 10.1007/s10750-020-04399-4
|View full text |Cite
|
Sign up to set email alerts
|

Flow intermittency negatively affects three phylogenetically related shredder stoneflies by reducing CPOM availability in recently intermittent Alpine streams in SW-Italian Alps

Abstract: Several Alpine streams are currently facing recurrent summer drying events with detrimental consequences on stream detritivores, i.e., shredders, due to negative effects via changes the organic matter (CPOM) availability. We examined the ecological requirements of three phylogenetically related shredder genera belonging to the family of Nemouridae (Plecoptera), namely Nemoura, Protonemura and Amphinemura, in 14 Alpine streams recently facing recurrent summer flow intermittency events. We evaluated the overlap … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Here, it is interesting to note that Nemouridae have no results in highly intermittent streams in summer and autumn, perhaps reflecting a complete exclusion from drying sites due to their high degree of rheophily (Tachet et al 2010). Nemouridae are also often described as shredders (Piano et al 2020), although the high degree of reliance on periphyton we estimated (> 50% in spring) suggests that the high‐altitude species sampled here are facultative rather than obligate consumers of terrestrial organic matter. Nemouridae may therefore feed on algae in spring when competition with other rheophilic grazers (i.e., Ephemeroptera) is low, switching to leaf litter during peak abscission periods in autumn.…”
Section: Discussionmentioning
confidence: 64%
“…Here, it is interesting to note that Nemouridae have no results in highly intermittent streams in summer and autumn, perhaps reflecting a complete exclusion from drying sites due to their high degree of rheophily (Tachet et al 2010). Nemouridae are also often described as shredders (Piano et al 2020), although the high degree of reliance on periphyton we estimated (> 50% in spring) suggests that the high‐altitude species sampled here are facultative rather than obligate consumers of terrestrial organic matter. Nemouridae may therefore feed on algae in spring when competition with other rheophilic grazers (i.e., Ephemeroptera) is low, switching to leaf litter during peak abscission periods in autumn.…”
Section: Discussionmentioning
confidence: 64%
“…Functional feeding traits could explain some of the shifts we observed in macroinvertebrate assemblages: shredder (Limnephilidae) and scraper (Heptageniidae) densities were lower and generalist collector gatherer (Chironomidae) densities were higher in the RC compared to the MC. Studies from other flow experiments in alpine intermittent streams found similar results (Piano et al, 2019(Piano et al, , 2020Siebers et al, 2020). The change in feeding mode could be mediated by a shift in basal resource quality in stream food webs; e.g., reduced microbial conditioning of terrestrial organic matter in drying alpine streams could lead to lowered lability for stream macroinvertebrates, or drying could reduce the productivity of algae in biofilms (Niedrist & Füreder, 2017;Siebers et al, 2019).…”
Section: Changes In Macroinvertebrate Assemblagesmentioning
confidence: 66%
“…Similar results were obtained by Piano et al (Piano, Doretto, Falasco, Fenoglio, et al, 2019; Piano, Doretto, Falasco, Gruppuso, et al, 2019) in Alpine streams and Datry et al (2011) in French Mediterranean rivers. In addition, Piano, Doretto, Falasco, et al (2020) demonstrated that in Alpine streams, recurrent seasonal droughts significantly altered CPOM availability, reduced shredder biodiversity and induced a shift in the ecological niche of some shredder species with consistent bottom‐up effect on the whole stream functionality. Although we did not directly assess the quantity of CPOM at P S and II S , we can reasonably assume that during the period of investigation a similar input of foliar material characterized both sites.…”
Section: Discussionmentioning
confidence: 99%